Access to Complex Abortion Care Service and Planning Improved through a Toll-Free Telephone Resource Line - Wendy V. Norman; Barbara Hestrin; Royce Dueck (Obstetrics and Gynecology International)
Background. Providing equitable access to the full range of reproductive health services over wide geographic areas presents significant challenges to any health system. We present a review of a service provision model which has provided improved access to abortion care; support for complex issues experienced by women seeking nonjudgmental family planning health services; and a mechanism to collect information on access barriers. The toll-free pregnancy options service (POS) of British Columbia Women’s Hospital and Health Centre sought to improve access to services and overcome barriers experienced by women seeking abortion. Methods. We describe the development and implementation of a province-wide toll-free telephone counseling and access facilitation service, including establishment of a provincial network of local abortion service providers in the Canadian province of British Columbia from 1998 to 2010. Results. Over 2000 women annually access service via the POS line, networks of care providers are established and linked to central support, and central program planners receive timely information on new service gaps and access barriers. Conclusion. This novel service has been successful in addressing inequities and access barriers identified as priorities before service establishment. The service provided unanticipated benefits to health care planning and monitoring of provincial health care related service delivery and gaps. This model for low cost health service delivery may realize similar benefits when applied to other health care systems where access and referral barriers exist.